2019
DOI: 10.22435/jek.18.2.1060.122-134
|View full text |Cite
|
Sign up to set email alerts
|

Phubbing, Penyebab Dan Dampaknya Pada Mahasiswa Fakultas Kesehatan Masyarakat, Universitas Indonesia

Abstract: ABSTRACT Nowadays, phubbing phenomena occur in various social groups, including college students. This has an impact on social relationships and physical health. This is a qualitative study which aims to describe the causes, behavior, and impact of phubbing. The informants were fifth semester Faculty of Public Heath, University of Indonesia undergraduate students’ year 2018. Data collected through focus group discussions on female students and in-depth interviews with male students. The results of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
0
0
6
Order By: Relevance
“…communication between the two parties. This is in line with the opinion that the phenomenon of phubbing is inherent In all circles, especially students, phubbing behavior shows disrespectful behavior and has an impact on communication between individuals when communicating (Amelia et al, 2019). The second informant whose initials IN came from the State Islamic University of North Sumatra revealed that:…”
Section: Don't Understand Phubbing Because This Is a New Thing I Hear...supporting
confidence: 73%
“…communication between the two parties. This is in line with the opinion that the phenomenon of phubbing is inherent In all circles, especially students, phubbing behavior shows disrespectful behavior and has an impact on communication between individuals when communicating (Amelia et al, 2019). The second informant whose initials IN came from the State Islamic University of North Sumatra revealed that:…”
Section: Don't Understand Phubbing Because This Is a New Thing I Hear...supporting
confidence: 73%
“…Uji Penelitian menyebutkan bahwa mahasiswa merupakan salah satu yang dominan aktif dalam penggunaan smartphone (Chiu, 2014). Perilaku phubbing khususnya pada mahasiswa merupakan topik penting di lingkungan akademis (Amelia et al, 2019). Hasil survey membuktikan bahwa mahasiswa cenderung sibuk dengan smartphone mereka daripada melakukan interaksi dengan orang lain (Yam & Kumcağız, 2020).…”
Section: Uji Normalitasunclassified
“…Alasannya karena phubber sangat individualis sehingga intensitas tatap muka atau kontak langsung akan berkurang (Aziz, 2019;Sirupang et al, 2020). Akibatnya, dia tidak sadar dengan apa yang terjadi di lingkungan sekitarnya, sulit membangun dan menjalin hubungan interpersonal, kurang mampu berkomunikasi verbal dengan baik, serta kehilangan kesempatan untuk bertemu dengan orang baru (Amelia et al, 2019;Mariati & Sema, 2019). Jika harus berinteraksi tatap muka, maka dia akan merasa kesepian dalam keramaian, tidak kooperatif (single fighter), dan tidak menghargai lawan bicaranya (Ivanova et al, 2020;Sirupang et al, 2020).…”
Section: Dampak Gawai Dan Phubbingunclassified